Neuroimmune interactions in painful TMD: Mechanisms and treatment implications. Issue 3 (29th July 2021) - Yi, Yating; Zhou, Xueman; Xiong, Xin; Wang, Jun
Abstract: The underlying mechanisms and treatment of painful temporomandibular disorders (TMDs) are important but understudied topics in craniofacial research. As a group of musculoskeletal diseases, the onset of painful TMD is proved to be a result of disturbance of multiple systems. Recently, emerging evidence has revealed the involvement of neuroimmune interactions in painful TMD. Inflammatory factors play an important role in peripheral sensitization of temporomandibular joint (TMJ), and neurogenic inflammation in turn enhances TMJs dysfunction in TMD. Furthermore, centralized neuroimmune communications contribute to neuron excitability amplification, leading to pain sensitization, and is also responsible for chronic TMD pain and other CNS symptoms. Therapeutics targeting neuroimmune interactions may shed light on new approaches for treating TMD. In this review, we will discuss the role of neuroimmune interactions in the onset of painful TMD from the peripheral and centralized perspectives, and how understanding this mechanism could provide new treatment options. Insights into the neuroimmune interactions within TMJs and painful TMD would broaden the knowledge of mechanisms and treatments of this multifactorial disease. Graphical Abstract: Reviews neuro-immune interactions that influence TMD pain sensitization and chronicity; describes the implications this has for treatment.